Sustained Release Matrix Tablet of Cisapride Drug to Treats Heartburn Caused by Gastroesophageal Reflux Disease (Gerd): A Detail Study Including Formulation, Evaluation and Optimization Aspects - Ram , Darshit; Kirtane, Santosh; Khilji , Rukhshar; Miniya , Priyanka; Bheda , Jagruti (Novel Aspects on Pharmaceutical Research Vol. 8, 2023)
Aim and Objective: Aim of present work is to prepare and evaluate sustained release matrix tablet of cisapride, due to short half life it is ideal candidate of sustained release drug delivery system and reduce the frequency of administration and to improve patient compliance. Dose of drug is 20 mg thrice a day by formulating sustained release matrix tablet using hydrogel polymers we can reduce once a day with better therapeutic effects. Materials and Methods: Direct compression method was used to formulate tablets, two polymers HPMC K4M and HPMC K100M using in formulation development. After matrix tablet preparation, tablet was evaluated with many tests including in vitro disintegration, dissolution and FTIR. 32 full factorial designs were implemented for optimizing formulation followed by kinetic analysis and stability study of optimized formulation. Results and Discussion: Consequences of Preformulation research of the Cisapride indicate that it has poor float belongings and compressibility property. To improve the glide and compressibility property, it became useful to use the without delay compressible grade additives within the formulation of tablet. Consequences of DSC examine proven that there's no exchange in drug’s melting peak after the education of tablet. Hydrophilic matrix of HPMC K4M and HPMC K100M in mixture sustained the Cisapride release effectively for more than 12h. The end result indicates that the mixture of HPMCK4M and HPMCK100M may be correctly, On the idea of the initial trials in the present look at a32 full factorial design changed into hired to take a look at the effect of unbiased variables, i.e. awareness of HPMCK4M(X1) and attention of HPMCK100M(X2) on dependent variables like% drug launch Q2, Q6 and Q10. Drug launch is also depending on the scale of matrix capsules so, size and surface location was stored consistent. Factorial batches F018, F019, F020, and F021 supply the f2 value seventy five-100. Factorial batch F019 offers the very best f2 fee 86.04 and also all of the hour’s drug release was within the targeted limits. Conclusion: The prepared formulation of Cisapride sustains release matrix tablet was stable and effective in treatment.